Optimized miR-124 reporters uncover differences in miR-124 expression among neuronal populations in vitro - Lepolard, Catherine; Rombaut, Cynthia; Jaouen, Florence; Borges, Ana; Caccomo-Garcia, Elodie; Popa, Natalia; Gascon, Eduardo (Frontiers in Neuroscience, 2023)
Introduction Although intensively studied in the last decades, how microRNAs (miRNAs) are expressed across different cell types in the brain remains largely unknown. Materials To address this issue, we sought to develop optimized fluorescence reporters that could be expressed in precise cellular subsets and used to accurately quantify miR contents in vivo. Results Focusing on miR-124, we tested different reporter designs whose efficiency was confirmed in different in vitro settings including cell lines and primary neuronal cultures from different brain structures. Unlike previous reporters, we provide experimental evidence that our optimized designs can faithfully translate miR levels in vitro. Discussion Tools developed here would enable assessing miRNA expression at the single cell resolution and are expected to significantly contribute to future miRNA research in vivo.